2008
DOI: 10.2106/jbjs.g.01556
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Assessment in Clinical Trials of Fracture-Healing

Abstract: Although there are numerous methods for defining fracture-healing in clinical studies, no consensus exists regarding the most valid and reliable manner for assessing union or for determining which outcomes are most important. This article summarizes and describes methods for the clinical assessment of fracture-healing and reports results from a systematic review of prevalent definitions currently used in published clinical studies. Conventional radiography and ad hoc clinical definitions continue to be the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
94
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 31 publications
1
94
1
1
Order By: Relevance
“…Serial orthogonal radiographs taken at 6 weeks, 3 months, and 6 months after the fracture were reviewed by one observer (CEH) who was not a treating surgeon, to assess union by identifying bridging callus of at least two cortices [12,22,23]. Patient charts were reviewed for documentation of the ability to bear weight without pain.…”
Section: Methodsmentioning
confidence: 99%
“…Serial orthogonal radiographs taken at 6 weeks, 3 months, and 6 months after the fracture were reviewed by one observer (CEH) who was not a treating surgeon, to assess union by identifying bridging callus of at least two cortices [12,22,23]. Patient charts were reviewed for documentation of the ability to bear weight without pain.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical parameters evaluated at the last followup were: (1) absence of pain or tenderness on palpation, (2) absence of pain when strength gripping, and (3) full range of motion at the adjacent joint. The three radiographic key parameters for the evaluation were: (1) bridging of the fracture site by bone, callus, or trabeculae; (2) bridging of the fracture seen at three cortices; and (3) obliteration of the fracture line or cortical continuity [15]. Each of the four observers independently evaluated each of the monthly radiographs to determine time of healing.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Although measures have been developed for hip and ankle fractures, 3 there is no validated measure that adequately describes functional healing for tibial fractures. 1 A recently published systematic review that evaluated variability in the assessment of fracture healing in orthopedic trauma studies reported that the 3 most commonly used clinical criteria were the absence of pain or tenderness on palpation or examination, the absence of pain or tenderness when bearing weight and the ability to bear weight.…”
mentioning
confidence: 99%
“…4 Similarly, another review evaluating the clinical criteria used to define fracture union found that the 4 most common criteria were the absence of pain or tenderness when bearing weight, the absence of pain or tenderness on palpitation or examination, the ability to bear weight and the ability to walk or perform activities of daily living with no pain. 2 Pain at the fracture site is commonly regarded as a sign that a fracture has not yet healed.…”
mentioning
confidence: 99%
See 1 more Smart Citation